Bioclimatic atlas of the terrestrial Arctic - Rantanen, Mika; Kämäräinen, Matti; Niittynen, Pekka; Phoenix, Gareth K.; Lenoir, Jonathan; Maclean, Ilya; Luoto, Miska; Aalto, Juha (Nature Publishing Group, 2023)
The Arctic is the region on Earth that is warming at the fastest rate. In addition to rising means of temperature-related variables, Arctic ecosystems are affected by increasingly frequent extreme weather events causing disturbance to Arctic ecosystems. Here, we introduce a new dataset of bioclimatic indices relevant for investigating the changes of Arctic terrestrial ecosystems. The dataset, called ARCLIM, consists of several climate and event-type indices for the northern high-latitude land areas > 45°N. The indices are calculated from the hourly ERA5-Land reanalysis data for 1950–2021 in a spatial grid of 0.1 degree (~9 km) resolution. The indices are provided in three subsets: (1) the annual values during 1950–2021; (2) the average conditions for the 1991–2020 climatology; and (3) temporal trends over 1951–2021. The 72-year time series of various climate and event-type indices draws a comprehensive picture of the occurrence and recurrence of extreme weather events and climate variability of the changing Arctic bioclimate.